Protective Media Composition and Freezing Regimen Experimental Substantiation During Mycobacterium Avium Freeze-Drying - Zavhorodnii , Andrii; Bilushko , Viktor; Kalashnyk, Mykola; Pozmogova , Svitlana; Paliy, Anatoliy; Pavlichenko , Olena (Problems of Cryobiology and Cryomedicine, 2023)
Probl Cryobiol Cryomed 2023; 33(2):139-143